Kualitas Produk dan Persepsi Harga terhadap Keputusan Pembelian - Bagus Imansyah; Hery Pudjoprastyono (Journal of Management and Bussines (JOMB), 2023)
The purpose of this study was to analyze the influence of product quality and price perceptions on smartphone purchasing decisions (a case study of East Java "Veteran" FEB UPN students. This research method uses quantitative research where the dependent variable is the purchase decision and the independent variable in this study is product quality and price perceptions. Sampling using Accidental Sampling consisted of 80 respondents and data analysis was carried out using the Partial Least Square (PLS) method. The results showed that product quality and price perceptions had a positive effect on purchasing decisions for Samsung smartphones at the Faculty of Economics and Business, National Development University " Veteran "East Java. In conclusion, product quality has good operating system performance for consumers so that it can influence purchasing decisions. Also, the better consumer perceptions of prices such as perceptions of affordability, price compatibility with product quality, price competitiveness, and ability provide benefits to be able to influence purchasing decisions on Samsung smartphone consumers. Keywords: Purchase Decision, Product Quality, Perceived Price